Retinal vasculopathy in patients with systemic lupus erythematosus. (October 2017) - Gao, N; Li, M T; Li, Y H; Zhang, S H; Dai, R P; Zhang, S Z; Zhao, L D; Wang, L; Zhang, F C; Zhao, Y; Zeng, X F
A retrospective case control study was conducted in the Peking Union Medical College Hospital. Medical records were reviewed for demographic data, clinical features, laboratory results, systemic lupus erythematosus (SLE) disease activity evaluations, and ophthalmic examinations to investigate the clinical characteristics and significance of retinal vasculopathy (RV) in Chinese patients with systemic lupus erythematosus. The prevalence of RV was approximately 0.66% (35/5298) in SLE patients. A total of 60 eyes were involved. The ocular presentations included decrease of visual acuity (48/60, 80%), visual field loss (7/60, 11.7%), and diplopia (3/60, 5%). Ophthalmic fundoscopic examination revealed cotton-wool spots (30/60, 50%), retinal vascular attenuation (31/60, 51.6%), and hemorrhages (41/60, 68.3%). Retinal angiogram showed that 72.7% (16/22) eyes had vaso-occlusion. The ophthalmic episodes could occur at any stage of SLE duration, with a median of 12 months (0–168 months) following SLE onset. Twenty-one (35%) eyes did not recover, or even worsened, during hospital stay. RV was found to be significantly associated with neuropsychiatric lesions (51.4% vs. 21.3%, p = .005) and hematological disturbance (62.9% vs. 34.3%, p = .005). SLE patients with RV had significantly higher SLE disease activity index scores than controls (19.9 ± 0.9 vs. 10.2 ± 0.7, p < .001). An inverse association of anti-SSA antibody with RV was detected (34.3% vs. 67.1%, p = .001). Nervous system disturbance (odds ratio (OR) = 4.340, 95% confidence interval (CI) 1.438, 13.094, p = .009) and leukocytopenia (OR = 6.385, 95% CI 1.916, 21.278, p = .003) were independent risk factors, while anti-SSA antibody positivity (OR = 0.249, 95% CI 0.087, 0.710, p = .009) was a protective factor for RV in SLE patients. In certain cases, RV is a threatening condition for SLE patients presenting with clinical ocular manifestations. Ophthalmo-fundoscopic detection is recommended as soon as SLE is diagnosed.